Criminal Responsibility for Children Who Perpetrate Serious Abuse to Achieve Justice In Society - Maharani, Febrianika (Universitas Negeri Gorontalo, 2023)
This article is an analysis of cases of serious abuse by child perpetrators, which were analyzed normatively using a statutory approach. The results of the analysis show that the age limit for criminal responsibility for children who commit serious abuse cannot be the same because each child has a different development process which affects their maturity in thinking. If the child's age is used as the only basis for consideration in deciding a child's case, then children who are perpetrators of criminal acts who are not yet 12 (twelve) years old cannot be given any sanctions in the form of actions or criminal penalties and to children who are not yet 14 (fourteen) old. years can only be given sanctions in the form of action. It is feared that this will become a legal loophole so that cases of crimes by children will continue to occur. The best interests of the child must be fought for for the child's optimal growth and development, but justice for the community, especially for the victim, must also be achieved, especially if the victim is also a child who must receive protection. Forensic psychologists are needed to assess and provide an overview of the psychological condition of children who have suffered serious abuse. So, when deciding on children's cases, the judge will refer to 2 (two) things, namely the age limit for criminal responsibility for children and the results of forensic psychological examinations. There is a need for reformulation in Article 21 paragraph (1) and Article 69 paragraph (2) of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System by adding the results of forensic psychological examinations as a basis for consideration in deciding juvenile cases.